Solvent-Free Microwave Extraction of Thymus mastichina Essential Oil: Influence on Their Chemical Composition and on the Antioxidant and Antimicrobial Activities - Araujo, André R.T.S. (2022)
This article belongs to the Special Issue Antiradical, Chemopreventive and Antimicrobial Analysis of Bioactive Substances